Modified Metal–Organic Frameworks as Efficient Catalysts for Lignocellulosic Biomass Conversion. (7th January 2021) - Lee, Jun Gyeong; Nam, Eonu; An, Kwangjin
Abstract : Biomass, a promising replacement for fossil fuels, can be used to produce eco‐friendly liquid fuels and chemicals. Various studies are investigating catalysts for lignocellulosic biomass conversion to valuable chemicals and fuels. Metal–organic frameworks (MOFs) are important catalysts because of their well‐ordered porous structures and large surface areas. Although MOFs can be applied directly, four modification strategies can be used to alter their catalytic properties and improve catalytic performance. In the first strategy, coordinatively unsaturated sites are created by changing the bonding state of the metal node. In the second approach, organic linkers with additional functional groups or active elements are used. In the third strategy, MOFs and other active elements are combined. In the final approach, MOFs are carbonized to produce carbon‐supported metal catalysts. We review the applications of modified MOFs for the catalytic conversion of biomass derivatives and discuss the factors that contribute to their improved catalytic performance. Abstract : This review provides several strategies for the modification of metal–organic frameworks (MOFs) as functional catalysts for lignocellulosic biomass conversion with high efficiency. Increasing the number of active sites of the MOF or binding of additional active species increases the catalyst conversion rate and improves the properties of the catalyst. In addition, stable carbon‐supported metal catalysts can be prepared through carbonization.